Pengaruh Pendapatan , Jumlah Nasabah Dan Tingkat Suku Bunga Terhadap Penyaluran Kredit Pt Pegadaian Cabang Kabupaten Jember Periode 2013 -2017 - Ratih Rachmawati (RELASI : JURNAL EKONOMI, 2019)
The research objective was to analyze the large number, number of customers, and interest rates on the loan distribution of PT Pegadaian Branch of Jember Regency.The type of data used in this study is secondary data consisting of time series data on income, number of customers obtained through the pawnshop office which is the object of research and interest rates for the period 2013-2017 obtained from BI which is the object of the research. The data is processed using computer software "SPSS 22" with multiple regression analysis methods. The Pawnshop Branch of Kabupaten Jember is very positive and significant towards lending to PT Pegadaian Branch of Kabupaten Jember, while the Interest Rate does not significantly influence the lending of PT Pegadaian Branch of Kabupaten Jember. Together, it focuses positively and significantly on the loan distribution of PT Pegadaian Branch of Jember Regency